2020
DOI: 10.1038/s41598-020-76360-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving the abrasion resistance of Ti6Al4V alloy by modifying its surface with a diazonium salt and attaching of polyurethane

Abstract: Commonly used endoprostheses in the orthopedic industry are those made of Ti6Al4V titanium alloy. Unfortunately, this material has low abrasion resistance, and therefore methods of their modification are still sought. A sensible approach is coating the alloy with a layer of a polymer having higher abrasion resistance. The adhesion of polymers to alloy is low, therefore the alloy requires prior modification. In this work, the alloy was modified with three types of diazonium salt and the influence of substituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Section 2.2 highlights several convenient, high-yielding reactions that deserve wider application for on-surface chemistry. Other similar reactions that have been successfully achieved on surfaces but remain underutilized, despite the ready commercial availability of the aniline precursor, include the coupling of isocyanates with hydroxyl groups or amines, to form urethane and urea functional groups, 85 and the Alder-ene reaction of triazolinediones with alkenes. 93 Two attractive reactions that, to our knowledge, have not been reported on anchor layers grafted from aryldiazonium ions are the para-fluoro-thiol reaction 209 and the inverse electron demand Diels−Alder reactions of tetrazines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Section 2.2 highlights several convenient, high-yielding reactions that deserve wider application for on-surface chemistry. Other similar reactions that have been successfully achieved on surfaces but remain underutilized, despite the ready commercial availability of the aniline precursor, include the coupling of isocyanates with hydroxyl groups or amines, to form urethane and urea functional groups, 85 and the Alder-ene reaction of triazolinediones with alkenes. 93 Two attractive reactions that, to our knowledge, have not been reported on anchor layers grafted from aryldiazonium ions are the para-fluoro-thiol reaction 209 and the inverse electron demand Diels−Alder reactions of tetrazines.…”
Section: Discussionmentioning
confidence: 99%
“…In work aimed at increasing the abrasion-resistance of Ti 6 Al 4 V, a widely used alloy for orthopedic implants, Sandomierski et al employed a layer-by-layer strategy to build up covalently anchored coatings of PU. 85 The preparation of a covalently linked sol−gel layer on gold was demonstrated by Bengamra et al, 54 who first coupled a silane to the surface through a thiol−yne photoclick reaction between a mercaptosilane and a grafted −Ph−CCH anchor layer. The workers then grew the sol−gel on the silanemodified surface by a reaction in a solution of aminosilane and tetraethoxysilane.…”
Section: Applicationsmentioning
confidence: 99%
“…The wellknown example of the polyaddition of diols to diisocyanates leading to polyurethanes has been illustrated on Ti 6 Al 4 V alloy previously modified using 4-hydroxymethylbenzendiazonium salts, in order to develop protective layers in endoprosthesis. 237,238 Also, a polyaddition based on successive 1,3-Huisgen cycloadditions of clickable diazido and diethynyl monomers allowed the construction of MWCNT-polymer nanocomposites at the surface of clickable azido-functionalized MWCNTs. 174…”
Section: Polymer Growthmentioning
confidence: 99%
“…5 Some applications of this alloy where good tribological performance is desirable are brakes in aircraft where the titanium alloy contacts steel, 1 and wear-resistant biomedical implants such as hip joints. 7,8…”
Section: Introductionmentioning
confidence: 99%
“…5 Some applications of this alloy where good tribological performance is desirable are brakes in aircraft where the titanium alloy contacts steel, 1 and wear-resistant biomedical implants such as hip joints. 7,8 Budinski 9 reported that though titanium alloys are often the most cost-effective corrosion-resistant material used in chemical industries, there are components in such systems which involve relative sliding, such as valves, where good wear resistance is also necessary. His study concluded that Ti6Al4V had poor abrasion resistance (poorer than soft 300 series stainless steel).…”
Section: Introductionmentioning
confidence: 99%